FOREIGN BODY IN AERO-DIGESTIVE TRACT: A DESCRIPTIVE ANALYSIS AT TERTIARY CARE TEACHING HOSPITAL - MAHICH, SUSHMA; SOLANKI, SUNIL; MATHUR, NAVNEET (Asian Journal of Pharmaceutical and Clinical Research, 2022)
Objectives: The objectives of the study were to analyze some of the key issues about the presentation, types, complications, and management arising about foreign body in the upper aero-digestive tract. Methods: All the patients presenting with or without history of swallowing or inhaling foreign bodies with symptoms such as dysphagia, drooling of saliva, stridor, and acute respiratory distress were included in study. Extraction of foreign body in airway tract was done by bronchoscopy and in digestive tract by esophagoscopy. Patient’s demographic details, types, symptoms and nature, size, and location of the inhaled foreign bodies were analyzed. Results: Patients aged more than 10 years constituted maximum number 14 (28%) in digestive tract. Patient aged 1–2 and 2–3 years accounted for most of the cases 10 (50%) in airway. Sensation dysphagia (100%) and foreign body sensation including cough (100%) were the most common symptom of digestive tract and airway tract, respectively. Currency coins (64%) were the most common type of foreign body in case of digestive tract ground nut (30%) was the most common type of airway foreign body. Conclusions: This study concluded that symptoms of foreign bodies in the aerodigestive tract are mainly nonspecific and needs high degree of suspicion, experience, and clinical acumen to diagnose and manage these patients.